1994
DOI: 10.1128/iai.62.7.2818-2824.1994
|View full text |Cite
|
Sign up to set email alerts
|

Production of gamma interferon by natural killer cells from Toxoplasma gondii-infected SCID mice: regulation by interleukin-10, interleukin-12, and tumor necrosis factor alpha

Abstract: Previous studies of mice have implicated natural killer (NK) cells as mediators of protective activity against Toxoplasma gondii through their production of gamma interferon (IFN-y). In the present study, we have compared NK-cell activity in infected and uninfected SCID mice. Our data reveal that infection results in increased levels of IFN-y in serum and elevated NK-cell activity but that these NK cells were not cytotoxic for T. gondii-infected P815 cells. Treatment with anti-IFN-y antibody abrogated the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
0
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(165 citation statements)
references
References 39 publications
(24 reference statements)
3
152
0
10
Order By: Relevance
“…This process leads to the accumulation of inflammatory cells, including mononuclear cells. Furthermore, TNFpotentiates the production of IFN-by NK cells in cooperation with IL-12 [15] and enhances the activation of T cells [45]. These biological activities of TNFmight be involved in its protective effect in cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process leads to the accumulation of inflammatory cells, including mononuclear cells. Furthermore, TNFpotentiates the production of IFN-by NK cells in cooperation with IL-12 [15] and enhances the activation of T cells [45]. These biological activities of TNFmight be involved in its protective effect in cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…TNFacts by activating polymorphonuclear leucocytes and macrophages to augment their antimicrobial potentials and triggers respiratory burst-and nitric oxide (NO)-dependent killing pathways [13,14]. Other studies have also demonstrated that TNFstimulates natural killer (NK) cells in cooperation with IL-12 to produce interferon-gamma (IFN-) [15], which plays an important role in early host defence mechanisms [16] and differentiation of Th1 cells [17]. The Th1 cells in turn generate large amounts of IFNand strongly potentiate macrophage antimicrobial activity [18], a central mechanism eliminating chronic infectious pathogens [19].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical study revealed that VCAM-1 and ICAM-1 are the two cerebrovascular endothelial adhesion molecules expressed in both wild-type and SCID mice during the chronic stage of infection. Although the cerebrovascular VCAM-1 expression following the infection is largely dependent on IFN-␥ (33), microglia in SCID and nude mice and NK cells are able to produce this cytokine in response to T. gondii (41,43,44). IFN-␥ production by these non-T cells appears to be sufficient to upregulate VCAM-1 expression on the cerebral vessels in infected SCID and nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…In SCID mice IFN-g, IL-12, TNF-a and TGF-b have important protective activities, whereas IL-6 and IL-10 increase the susceptibility of SCID mice to T. gondii (Hunter et al 1993, Gazzinelli et al 1994. It has been reported that in-vivo treatment with anti-ASGM1 reduces NK cell activity and serum levels of IFN-g in T. gondii infected SCID mice, though this does not result in earlier mortality (Hunter et al 1994). Therefore, in our model, it is possible that increased levels of murine IL-6 and IL-10, due to hu-PBL transplantation and decreased amounts of IFN-g, after the anti-ASGM1 depletion of NK cells, may contribute to the increased parasite burden in transplanted animals.…”
Section: Discussionmentioning
confidence: 99%